2016
DOI: 10.1093/bja/aew056
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparison of the Mallampati evaluation in neutral or extended cervical spine positions: a retrospective observational study of >80 000 patients

Abstract: This retrospective observational study demonstrates that cervical extension improves the specificity but decreases sensitivity of Mallampati examination. The Mallampati evaluation should be performed with the cervical spine in the neutral position to maximize test sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…When evaluating diagnostic tests a high sensitivity and specificity is desired, with the former being of greater importance [13]. Ultrasonography-derived indicators have been recently evaluated for the prediction of difficult airway.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating diagnostic tests a high sensitivity and specificity is desired, with the former being of greater importance [13]. Ultrasonography-derived indicators have been recently evaluated for the prediction of difficult airway.…”
Section: Discussionmentioning
confidence: 99%
“…A thick neck 15 , 28 , 190 - 192 and OSA 167 are associated with difficult DL or intubation. Whether obesity alone predicts difficult laryngoscopy/intubation continues to be controversial, with some studies reporting an association, 15 , 29 , 31 , 39 , 192 - 195 and others not. 11 , 25 , 191 , 196 - 198 No studies have yet reported obesity to be a risk factor for difficult or failed VL-facilitated tracheal intubation, although one study has reported a thick neck to be associated with failed HA-VL-facilitated tracheal intubation.…”
Section: Special Situationsmentioning
confidence: 99%
“…This binary risk assessment is then used to predict a research outcome of either difficult laryngoscopy or of difficult intubation. The commonly used standard for difficult laryngoscopy is a Cormack-Lehane direct laryngeal view classification of grade III or IV, 5,23,[25][26][27][28][29][30][31] although the percentage of glottic opening score has also been used. 32 When the chosen outcome is instead difficult intubation, this has been coded as either a numeric threshold (eg, 3 or more unsuccessful attempts 26 ) or a composite score based on the number of attempts and ultimate intubation failure.…”
Section: How Well Does the Mallampati Score Predict Difficult Laryngomentioning
confidence: 99%
“…Healy et al 26 performed the third largest Mallampati study, with 80,801 anesthetics, and found that a Mallampati score of III or IV was 43% sensitive and 83% specific in predicting difficult laryngoscopy. There were 14 false-positive warnings for each correct prediction of a difficult airway.…”
Section: How Well Does the Mallampati Score Predict Difficult Laryngomentioning
confidence: 99%
See 1 more Smart Citation